Fault-tolerant control strategy for actuator faults using LPV techniques: application to a two degree of freedom helicopter - Montes De Oca, Saúl; Puig, Vicenç; Witczak, Marcin; Dziekan, Łukasz (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a Fault Tolerant Control (FTC) strategy for Linear Parameter Varying (LPV) systems that can be used in the case of actuator faults is proposed. The idea of this FTC method is to adapt the faulty plant instead of adapting the controller to the faulty plant. This approach can be seen as a kind of virtual actuator.
Keywords: fault-tolerant control; linear parameter varying; virtual actuator; linear matrix inequality